(untitled) (Research, Society and Development, 2022)
Objective: This paper aims to carry out the content validation of nursing care protocol in pediatric hematopoietic stem cell post-transplantation. Method: Methodological research was used with the participation of Brazilian judges (n=15) by the Delphi technique in two rounds, from January 2019 to October 2020. The judges’ suggestions were evaluated in consensus meetings and complied. The data were analyzed by Content Validity Index, Kappa coefficient, and Cronbach’s alpha coefficient. Results: The nursing care protocol is composed of three dimensions of nursing problems, that are, psychobiological (including thirty nursing problems), psychosocial (comprising seven nursing problems), and psychospiritual (with three nursing problems). In the second round of the protocol evaluation, the Kappa coefficient was equal to 0.70, the Cronbach’s alpha coefficient was 0.94, and the overall Content Validity Index was 0.98. Conclusion: The protocol content was considered valid. This technology can be safely used in the transplanted child care.